Strategi Peningkatan Daya Saing Saham dan Obligasi Syariah dalam Menghadapi Masa Pandemi dengan Metode SWOT - Aditya Bimantara; Ummi Ainun Nadhiroh; Erlina Komaruljannah (Jurnal Ilmiah Ekonomi Islam, 2021)
The COVID-19 outbreak has had an impact on various aspects throughout the world, especially in the economic field. The decline in state income and the threat of financial stability for both corporations and households continue to trigger an increase in the poverty rate in Indonesia. Regardless of the government's efforts, the public has changed their financial management style to invest in the Islamic capital market. This research aims to analyze strategies to increase the competitiveness of several Islamic capital market instruments, namely Islamic stocks and bonds (sukuk) during the pandemic. The main problem answered in this research is how Islamic stocks and bonds (sukuk) are able to increase the competitiveness of the Islamic capital market in Indonesia. The method used in this research is SWOT analysis with qualitative data types obtained from secondary data sources. This research concludes that the main strategy is to increase the marketing and socialization of Sharia investment products to the public, as well as add sharia securities and instrument development programs to expand the Sharia product mix in accordance with the applicable legal basis. Therefore, the strategy obtained is expected to be an input for Islamic stock and bond companies and other relevant stakeholders.